Improvement of steam oxidation resistance of the γ-TiAl alloy with microarc oxidation coatings at 900–1200 ℃. (December 2022) - Xu, Chi; Zhu, Minghao; Guan, Haohao; Gao, Chuanli; Jin, Xiaoyue; Du, Jiancheng; Xue, Wenbin
Abstract: A dense ceramic coating of ∼30 µm on the γ-TiAl alloy was fabricated using the microarc oxidation (MAO) technique. The coated alloy was oxidized under 900–1200 ℃ steam environments for 3600 s. The oxidation rate for the MAO-coated TiAl alloy is significantly lower than the pristine TiAl alloy. The MAO coating remains intact through the oxidation tests, while the layered structures are formed beneath the MAO coating, which are characterized in detail with X-ray diffraction, scanning and transmission electron microscopy. The improvement of steam oxidation resistance is attributed to the barrier effect of the MAO coating. Highlights: A dense ceramic coating is fabricated on the γ-TiAl alloy with micro-arc oxidation technique. The coated TiAl alloy show improved oxidation resistance in water steam at 900–1200 ℃. The ceramic coating stays intact and multilayered structures are formed beneath it after the steam oxidation tests. The amorphous SiO2 phase in the MAO coating is crystalized after oxidation tests. The Al2 TiO5 and SiO2 phases play important roles in the anti-corrosion mechanism.